BOOK REVIEW Imam Abdul Hamid Al-Ghazali (Imam Ghazali). Ihya Ulum Id-Din (Revival of Religious Learning), Vol. 1. The Book of Worship. Translated by Fazlul Karim. Darul Ishaat, Urdu Bazar, Karachi, Pakistan, 1993 - Choudhury, Masud (Journal of Critical Realism in Socio-Economics (JOCRISE), 2023)
Sheikh al-Islam, Imam Abdul Hamid Al-Ghazali was born in 1058AD in the city of Tus, in Persia at that time. He died in the year 1111AD in this same city. The translator of the above-mentioned work writes: “Imam Abu-Hamid al-Ghazali is unquestionably the greatest theologian of Islam and one of its noblest and most original thinkers. He reproduced in his religious experience all the spiritual phases developed by Islam. It is therefore appropriate to inquire in this work and in many other ones that he has contributed to the pale of Islamic thought and worship (ibadah) as to what constitutes the centric focus of Islam regarding self and the world-system of Islamic belief and construction.